Inobservancia de la normativa que protege al adulto mayor frente al maltrato que sufre dentro de su entorno social y familiar - Sánchez Campoverde, Tatiana Paola (2016)
It is true that when we speak of the elderly, can invoke a number of legal texts containing provisions to benefit the people who have reached 65 years; automatically it comes to mind that adage as suggested priority and special attention to this vulnerable group. But is there a law effectively structured to ensure the dignified survival of the elderly? While it is true our society is enjoying a bit of big changes that drive progress, one being the focus and attention has been taken to the different expressions of abuse against the most vulnerable groups in society; beginning with the Norman protection offered to children and adolescents, women, people with special or limited capabilities; there is a vulnerable group that is going somewhat unnoticed seniors…….